If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4)(7x + 5) = 0 Reorder the terms: (-4 + 3x)(7x + 5) = 0 Reorder the terms: (-4 + 3x)(5 + 7x) = 0 Multiply (-4 + 3x) * (5 + 7x) (-4(5 + 7x) + 3x * (5 + 7x)) = 0 ((5 * -4 + 7x * -4) + 3x * (5 + 7x)) = 0 ((-20 + -28x) + 3x * (5 + 7x)) = 0 (-20 + -28x + (5 * 3x + 7x * 3x)) = 0 (-20 + -28x + (15x + 21x2)) = 0 Combine like terms: -28x + 15x = -13x (-20 + -13x + 21x2) = 0 Solving -20 + -13x + 21x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -7x)(4 + -3x) = 0Subproblem 1
Set the factor '(-5 + -7x)' equal to zero and attempt to solve: Simplifying -5 + -7x = 0 Solving -5 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -7x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = 0 + 5 -7x = 0 + 5 Combine like terms: 0 + 5 = 5 -7x = 5 Divide each side by '-7'. x = -0.7142857143 Simplifying x = -0.7142857143Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {-0.7142857143, 1.333333333}
| 4y+10=180 | | x+32=3x+24 | | -3(8-7n-2)=18 | | 12f-15=12f-15 | | 14+8m=14-3m-5 | | 16m+4x=y | | 10x^2-36x+27=0 | | 3x-2x-4=17 | | 2(x-5)-(3x+6)=-13 | | In(3x)+In(2x)=3 | | 3(5x+4)+12=-8 | | V=pir | | 20y=13000 | | 10-3s=s | | 2(x-5)-(3x+6)=-12 | | -1=-6x+5x+5 | | 4x-2x+4=24 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=f(x) | | -1=-6x | | 3x+-7=8+6(x+2) | | 8n-1(2n-3)= | | -5n-7=3n+41 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=0 | | 4p=63 | | 4(y-1)=4 | | 12=0.25(R) | | 6x^2+21x= | | 9(2m-3)-4(5+3m)=5 | | 4n+3+n=43 | | 4(x-4)+3(1+5x)=-32 | | 22=-was | | 36=-9(6+1) |